Overview of Public Policies focused on socio-environmental issues implemented by Municipal Environment Secretariats in the southeast region of Pará (Research, Society and Development, 2021)
The objective of this study was to analyze the challenges that the municipalities of the micro region of Paragominas, in the southeastern region of Pará, are facing when implementing public policies related to socio-environmental issues, seeking to understand the dynamics of the Municipal Secretariats of Environment. The research is based on a qualitative and quantitative approach, statistical analysis and data interpretation based on the elaboration of figures and tables in Excel software. Regarding the results obtained, it is noted that 100% of the surveyed municipalities implemented the Environmental Policy and technical team for environmental licensing, which are important for the implementation of public policies, however, the total implementation of the technical team for inspection and implementation of information did not show unanimity, although they are important to ensure compliance with the legislation. It was observed that 100% of the municipalities joined the Green Municipalities Program. Regarding the main sources of revenue, 100% of the municipalities have implemented the Municipal Environment Fund and also manage it, however, the Green ICMS is not unanimous in the implementation of the Law, as well as the management of its resources, although this be an important source of revenue. The main public policies developed were the implementation of landfills and actions to recover degraded areas. The main licensed activities were agriculture and livestock, indicating producers' interest in legality. The main actions of environmental education were the lectures. Although the municipal secretariats that make up the studied micro-region face challenges and limitations for the effective implementation of public policies, there is an effort to promote environmental improvement.